Generation of incoherent light from a laser diode subject to external optical injection from a superluminescent diode - Takamizawa, Akifumi; Yanagimachi, Shinya; Ikegami, Takeshi (Applied optics. Optical technology and biomedical optics, 2014)
In this study, incoherent light with a spectral linewidth of 7 nm and 140 mW of power was generated from a laser diode (LD) into which incoherent light emitted from a superluminescent diode was injected with 2.7 mW of power. The spectral linewidth of the light from the LD was broadened to 12 nm when the diode's output power was reduced to 15 mW. In the process of transformation from single-mode laser light to incoherent light with a broad spectrum by increasing injection-light power, multimode laser oscillation and a noisy spectrum were found in the light from the LD. This optical system can be used not only for amplification of incoherent light but also as a coherence-convertible light source.